2012
DOI: 10.5999/aps.2012.39.5.489
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Oncoplastic Volume Replacement Techniques after Breast Conserving Surgery in Small to Moderate-sized Breasts

Abstract: BackgroundIn Korean women, many of whom have small to moderate-sized breasts, it is difficult to cover a partial breast defect using oncoplastic volume displacement techniques after removal of an adequate volume of tissue during oncologic surgery. In such cases, oncoplastic volume replacement techniques are more useful.MethodsFrom January 2007 to December 2011, 104 women underwent a total of 107 breast-conserving surgeries with various kinds of oncoplastic volume replacement techniques. We used latissimus dors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 15 publications
(17 reference statements)
1
29
2
1
Order By: Relevance
“…Our hospital has made consistent efforts to establish algorithms for breast reconstruction techniques applicable to different types of patients, depending on the excised mass [ 7 , 8 ]. Since Korean women have smaller breasts than their western counterparts, lumpectomy often results in significant breast deformity as the residual breast tissue is minimal [ 7 ]. Volume replacement (VR) techniques can overcome this limitation and provide sufficient volume, and stable aesthetic results.…”
Section: Introductionmentioning
confidence: 99%
“…Our hospital has made consistent efforts to establish algorithms for breast reconstruction techniques applicable to different types of patients, depending on the excised mass [ 7 , 8 ]. Since Korean women have smaller breasts than their western counterparts, lumpectomy often results in significant breast deformity as the residual breast tissue is minimal [ 7 ]. Volume replacement (VR) techniques can overcome this limitation and provide sufficient volume, and stable aesthetic results.…”
Section: Introductionmentioning
confidence: 99%
“…13,[16][17][18] Other authors support the use of the TDAP flap for defects in all quadrants. 14,15,19 The advantage of the TDAP flap over the latissimus flap is decreased morbidity and predictable volume. Compared with the ICAP flap, the TDAP flap has greater pedicle length and is easier to inset.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have noted improved patient satisfaction and outcomes with oncoplastic techniques. 6,25 General satisfaction scores reported by patients reached 87% with immediate flap reconstruction 14,15 Spiegel et al reported that 11 out of 12 (91%) patients graded their result as good to excellent after free flap partial breast reconstruction, with only one grade of "fair" due to dissatisfaction with intra-flap fat necrosis resulting from revision liposuction. 9 With 60 to 70% of early-stage breast cancers treated with BCT and 20 to 30% of them having fair to poor aesthetic outcomes, the number of patients who could benefit from oncoplastic reconstruction is potentially as large as that undergoing mastectomy with reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…LD flap breast reconstruction is a procedure that uses autologous tissues and is often used for breast reconstruction following a mastectomy among Asian women with small to moderate-sized breasts [4,5]. The surgical technique has advanced over time with many surgeons choosing to use the procedure, and reports on complications associated with the procedure have been decreasing [6][7][8].…”
Section: Discussionmentioning
confidence: 99%